Managing international development adaptively – a cultural shift. Issue 2 (17th February 2022) - Leeds, Rachel; Palaia, Anne
ABSTRACT: Adaptive management is critical for implementing international development programmes in complex, unpredictable environments. This paper was motivated by the apparent disconnect between the structures and processes that shape procurement and the trend toward more adaptive models of programming in development organisations. Its primary target audience is donor organisations, and it will focus on the responsibility of the donor as an enabler of adaptation. It first presents a definition of adaptive management, and then describes how procurement has evolved to enable more adaptive management. It concludes with a discussion of the untapped potential for adaptive management to shape donor-partner relationships.